Cytotoxicity, Biocompatibility, and Biomineralization of the New High-plasticity MTA Material - Cintra, Luciano Tavares Angelo [UNESP] (2017)
Introduction Mineral trioxide aggregate (MTA) has excellent biological properties, but its handling properties have been criticized for both ProRoot MTA (Tulsa Dental Products, Tulsa, OK) and white MTA-Angelus (MTA-Ang; Angelus Indústria de Produtos Odontológicos S/A, Londrina, PR, Brazil). Angelus MTA HP (high plasticity) (Angelus Indústria de Produtos Odontológicos S/A) has been introduced recently. Considering the importance of biological properties of materials that will be in contact with the tissues, this study evaluated the cytotoxicity, biocompatibility, and biomineralization of MTA HP compared with white MTA-Ang. Methods L929 fibroblast cell lines were cultured, and cell viability was assessed at 6, 24, 48, and 72 hours using the alamar Blue assay (Thermo Fisher Scientific, Waltham, MA). A subcutaneous implant test was performed with polyethylene tubes containing 1 of the materials or empty tubes (control) using 20 Wistar rats. After 7 and 30 days of implantation, the tubes with surrounding tissues were removed for analysis using hematoxylin-eosin or von Kossa stain or they remained unstained for observation under polarized light. The results were statistically analyzed (P < .05). Results A significant increase in cell viability for MTA HP was observed after 24, 48, and 72 hours compared with the control (P < .05). At 72 hours, MTA HP exhibited a higher viability compared with white MTA-Ang (P < .05). Histologic analysis performed at 7 days showed moderate inflammation and a thick fibrous capsule in all groups (P > .05). At 30 days, mild inflammation and a thin fibrous capsule were observed in all groups (P > .05). All materials had structures positive for von Kossa and birefringent to polarized light. Conclusions MTA HP showed biocompatibility and biomineralization similar to MTA-Ang. In addition, MTA HP showed increased fibroblast cell viability compared with white MTA-Ang after a longer period.